Strategi Pemasaran Islam pada UMKM (Studi Pada Kantin Ibun dan Geprek Arya, Lampung Timur) - Sri Cahyati Utami; Tria Septiani; Lilis Renfiana (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Islamic marketing strategy is one of the muamalah practices and every business sector must implement it, although the methods are different, starting from the chosen market segmentation, targeting or positioning. The research is research with a qualitative approach. The data taken is primary and secondary data, through observations and interviews with two business actors engaged in the food business, namely Kantin Ibun and Geprek Arya. These two business actors have implemented Islamic marketing strategies well and implemented monotheism, justice and honesty. The market segmentation of both is the same, namely selling food products with the target being the local community by providing friendly service and highlighting the quality of each product.